Mechanical characterisation of alginate-gelatin hydrogel for 3D bioprinting applications - Han, Jefferson ShengChou (2014)
In recent years, 3D bioprinting has caught the attention of the medical community for its potential to provide valuable solutions to patients in urgent need of tissue or an organ replacement. Limited by the availability of a compatible organ donor, surgeons may resort to 3D bioprinting to produce tissues or organs to meet the patients’ need. However there are some limitations faced by the 3D bioprinter including structures and designs that can be printed by the 3D Bioprinter may have limited resolution and mechanical strength [1]. Therefore the motivation of this project is to explore and optimise alginate-gelatin hydrogel properties to create a suitable hydrogel that have excellent resolution and mechanical strength for bioprinting purpose and applications. Alginate-gelatin combination was selected for the project among other types of hydrogel including agarose-gelatin and alginate-calcium sulphate, due to the fact that alginate-gelatin demonstrates better printability on initial testing. Mechanical properties were more consistent throughout the hydrogel, giving shape retention to the printed structure. The alginate-gelatin hydrogel was tested for optimal temperature for bioprinting and ideal alginate to gelatin concentration for printing structures with maximum resolution. In addition, characterisation of the hydrogel was performed to determine the mechanical properties. This includes hydrogel degradation by area and weight, viscosity of the hydrogel, dynamic mechanical analysis, hydrogel pH, swelling properties and cell viability upon printing. Results shows the 1 layer printed hydrogel scaffold (450μm thickness) with and without cells is able to maintain both structure and integrity for a duration of 13 days, despite incubation. Maximum swelling experienced by the hydrogel is 8% increase in the total hydrogel mass. This is favourable in comparison to other research done which shows swelling of 40% to 170%. The pH of the alginate-gelatin hydrogel was tested to be 5.4 using the pH meter. However, despite the low pH, cells are shown to be viability before and after printing process. Overall the results are promising as it suggest that the optimized alginate-gelatin hydrogel is able to be compatible for printing fine resolution 3D hydrogel structures with adequate mechanical strength useful for printing future applications of tissues/organs.